Detecting spatiotemporal clusters of dementia mortality in the United States, 2000–2010. (November 2018) - Xu, Wei; Wu, Changshan
Highlights: We used complete geocoded national death certificate data during 2000 and 2010 in our analysis. We differentiated Alzheimer's disease and all-cause dementia to mitigate effects of dementia subtypes on cluster results. Low risk clusters were found in the Northeast and high risk clusters were in the Ohio River Valley and Carolinas. Men and women showed similar Alzheimer's disease/dementia cluster patterns. Improvement in relative risk of Alzheimer's disease/dementia mortality exists in highly likely clusters over the decade. Abstract: Based on national death certificate data during 2000 and 2010, we employed the space-time scan statistic to identify spatiotemporal clusters of dementia mortality in the contiguous United States. Results revealed that, for both Alzheimer's disease and all-cause dementia mortality in the total population, the most likely clusters occurred in the Northeast region, with lower than average relative risk. The most likely excess mortality clusters were in the Pacific Northwest and Ohio River Valley and Carolinas. Temporal information of clusters suggested reduction in the relative risk of Alzheimer's disease and all-cause dementia mortality in most of the highly likely clusters. The results should propel public health agencies to evaluate the capacity of local health and social care to meet dementia patients' needs before death in the high-risk cluster areas. Further investigation of causal factors of these clusters is needed.